Duodenal Adenocarcinoma of Brunner Gland Origin: A Case Report - Ji Hye Moon; Kyoungbun Lee; Han-Kwang Yang; Woo Ho Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2018)
We report a case of adenocarcinoma originating from the duodenal Brunner glands in a 47-year-old female patient. The lesion was 0.8 cm in extent and located at the posterior wall of the first part of the duodenum. Histologically, the tumor showed transition from non-neoplastic Brunner glands through dysplastic epithelium into adenocarcinoma. The carcinoma cells were strongly positive for MUC6 protein, which is an epithelial marker for the Brunner glands. Tumor protein p53 was overexpressed in the carcinoma cells, but not in the non-neoplastic or dysplastic epithelium. Dystrophic calcification was predominant. This is the first case report of duodenal adenocarcinoma of Brunner gland origin in Korea.